Ayahuasca Improves Self-perception of Speech Performance in Subjects With Social Anxiety Disorder: A Pilot, Proof-of-Concept, Randomized, Placebo-Controlled Trial - Dos Santos, Rafael G; Osório, Flávia de Lima; Rocha, Juliana Mendes; Rossi, Giordano Novak; Bouso, José Carlos; Rodrigues, Lucas S; de Oliveira Silveira, Gabriela; Yonamine, Mauricio; Hallak, Jaime E Cecílio (Journal of clinical psychopharmacology, 2021)
Ayahuasca is a classic hallucinogen with anxiolytic and antidepressive properties. Anecdotal evidence also suggests that it improves performance (eg, singing, speech). This controlled trial assessed the effects of ayahuasca on speech performance and anxiety in individuals with social anxiety disorder. Seventeen volunteers with social anxiety disorder participated in a pilot, proof-of-concept, randomized, parallel-group trial. Self-perception of performance during a public-speaking test was assessed with the Self-statements During Public Speaking Scale primary outcome). Secondary outcomes included anxiety/subjective effects (Visual Analog Mood Scale; Bodily Symptoms Scale), recognition of emotions in facial expressions (REFE), tolerability measures (cardiovascular measures, self-reports), and brain-derived neurotrophic factor plasma levels. Effects on anxiety and REFE were assessed again 7, 14, and 21 days postdrug. Compared with placebo, ayahuasca significantly improved self-perception of speech performance (Self-statements During Public Speaking Scale) and increased somatic symptoms (Bodily Symptoms Scale). There was also a significant time × group interaction in the cognitive deterioration Visual Analog Mood Scale factor and a significant effect of time in the REFE task, especially in reaction time. Other measures were not significantly modified. Ayahuasca was well tolerated, producing mainly nausea, gastrointestinal discomfort, and vomiting. Ayahuasca improved self-perception of speech performance in socially anxious individuals. These effects occurred independent of task-related anxiety and REFE, suggesting that ayahuasca could specifically improve the cognitive aspect of speech performance. Further studies should try to unveil the mechanisms involved in the effects of ayahuasca and to better understand its effects on anxiety.